NPK and flavonoids affecting insect populations in Dimorphandra mollis seedlings - doi: 10.4025/actasciagron.v34i1.11233 (Acta Scientiarum. Agronomy, 2011)
The study evaluated the influence of different levels of nitrogen (N), phosphorus (P) and potassium (K), and flavonoids on the population of insects in Dimorphandra mollis Benth (Leguminosae) seedlings. The treatments associated with the highest level of attacks by Frankliniella schulzei (Trybon) (Thysanoptera: Thripidae) were 600 mg dm-3 of P and 50 mg dm-3 of K. The highest level of attacks by Coccidae occurred for 300 of P and 150 and 250 mg dm-3 of K. The last two treatments also exhibited the highest level of attacks by Pseudococcidae. On the other hand, the control exhibited higher levels of flavonoids and a lower level of insect attacks. We observed a small positive effect of N levels on attack by F. schulzei. The levels of N, P and K negatively affected the levels of flavonoids in the leaves of D. mollis. We detected no significant effects of flavonoid levels on the populations of Coccidae, Pseudoccocidae and            F. schulzei. Higher numbers of Coccidae and Pseudococcidae were observed in the abaxial face of apical leaves. However, higher numbers of F. schulzei were observed on the adaxial face at lower heights in the canopy. The preferred treatment for the production of D. mollis seedlings is the control (without fertilization) because it showed higher flavonoid levels than other treatments and did not result in higher insect numbers.